KONSEP LABA BERKAH DALAM PERDAGANGAN SYARIAH - Zaen Udin Mansyur (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2022)
Abstract: This study examines the concept of blessing profit, widely discussed by observers of the Islamic economy and claimed as an abstract matter. It has made its measurement nearly impossible without proper criteria. Using a descriptive analysis method to examine more profound matters that need to be done by both traders and buyers, this study shows that there are several matters that business people must carry out to obtain blessing profits, namely through the business preprocessing, process, and post-process stages. In the preprocessing stage, traders and buyers must possess theological values, which appear on a high devotion to God. In the following stage, the trade process is strengthened by instilling an honest, sincere, professional, friendly social, and generous attitude. This honest attitude will be shown in a sincere attitude of both parties and, in turn, a professional attitude will smoothen the activities, shown by increasing the number of customers along with an intense meeting (silaturrahim) and generosity. In the final stage, the acquired blessed profits are strengthened by evaluating trading activities and calculating profits to determine the amount of zakat that must be paid if the profit has reached the nisab.Abstrak: Tujuan penelitian ini adalah mengkaji konsep laba berkah yang banyak dibicarakan oleh para pemerhati ekonomi syariah yang diklaim sebagai perkara yang sangat abstrak, sehingga mengukurnya menjadi aktivitas yang sangat sulit, kecuali melalui kriteria-kriteria yang tepat. Penelitian ini menggunaka metode analisis deskriptif untuk mengkaji lebih mendalam tentang perkara-perkara yang wajib dilakukan oleh para pelaku perdagangan baik itu pedagang maupun pembeli untuk mencapai laba berkah tersebut. Hasil penelitian ini menunjukkan bahwa ciri-ciri pelaku bisnis memperoleh laba berkah dapat dilihat dari mulai tahap praproses, proses, dan pascaproses berbisnis. Pada tahapan praproses, seorang pebisnis diwajibkan mendasari sikap berdagangnya dengan nilai-nilai teologis dengan harapan dapat melahirkan pengabdian yang tinggi terhadap yang kuasa. Di tahapan berikutnya, proses berbisnis diperkuat dengan penanaman sikap yang jujur, ikhlas, professional, ramah, dan murah hati. Sikap jujur ini akan mendorong lahirnya sikap ikhlas kedua belah pihak dan melahirkan sikap profesional, sehingga aktivitas dagang berjalan dengan lancar yang ditandai dengan bertambahnya pelanggan dari waktu ke waktu. Tahapan akhir, perolehan laba berkah diperkuat melalui evaluasi aktivitas perdagangan, menghitung laba untuk mengetahui jumlah zakat yang harus dibayarkannya, jika laba tersebut telah mencapai nisab.